Pengaruh Profitabilitas, Kompensasi Bonus Dan Ukuran Perusahaan Terhadap Praktik Perataan Laba - Nelyumna; Nursari; Sri Ambarwati (Jurnal Ekonomi, 2022)
This research aims to examine and analyze the effect of profitability, bonus plan and firm size on Income Smoothing. Index Excel (1981) model is used to determine the income smoothing practices. This research method uses quantitative descriptive methods. The data used is secondary data from the population using the Food and Beverages Sub Sector Manufacturing Company listed on the Indonesia Stock Exchange for the period 2017-2020. The hypotheses were tested using logistic regression analysis to examine the influence of these variables on income smoothing processed using SPSS ver25. The Sample was determined using purposive sampling obtained by 10 company samples, for a total of 40 observational data. The results of this study showed that profitability has a positive effect on income smoothing, a bonus plan negative effect on the action of income smoothing, while firm size has no effect on income smoothing.